Mode of Delivery and Long‐Term Health‐Related Quality‐of‐Life Outcomes: A Prospective Population‐Based Study. Issue 2 (14th November 2016) - Petrou, Stavros; Kim, Sung Wook; McParland, Penny; Boyle, Elaine M.
Abstract: Background: Relatively little is known about the effects of mode of delivery on long‐term health‐related quality‐of‐life outcomes. Furthermore, no previous study has expressed these outcomes in preference‐based (utility) metrics. Methods: The study population comprised 2, 161 mothers recruited from a prospective population‐based study in the East Midlands of England encompassing live births and stillbirths between 32 +0 and 36 +6 weeks' gestation and a sample of term‐born controls. Perinatal data were extracted from the mothers' maternity records. Health‐related quality‐of‐life outcomes were assessed at 12 months postpartum, using the EuroQol Five Dimensions (EQ‐5D) measure with responses to the EQ‐5D descriptive system converted into health utility scores. Descriptive statistics and multivariable analyses were used to estimate the relationship between the mode of delivery and health‐related quality‐of‐life outcomes. Results: The overall health‐related quality‐of‐life profile of the women in the study cohort mirrored that of the English adult population as revealed by national health surveys. A significantly higher proportion of women delivering by cesarean delivery reported some, moderate, severe, or extreme pain or discomfort at 12 months postpartum than women undergoing spontaneous vaginal delivery. Multivariable analyses, using the Ordinary Least Squares estimator revealed that, after controlling for maternal sociodemographic characteristics, cesarean delivery without maternal or fetal compromise was associated with a significant EQ‐5D utility decrement in comparison to spontaneous vaginal delivery among all women (−0.026; p = 0.038) and among mothers of term‐born infants (−0.062; p < 0.001). Among mothers of term‐born infants, this result was replicated in models that controlled for all maternal and infant characteristics (utility decrement of −0.061; p < 0.001). The results were confirmed by sensitivity analyses that varied the categorization of the main exposure variable (mode of delivery) and the econometric strategy. Conclusions: Among mothers of term‐born infants, cesarean delivery without maternal or fetal compromise is associated with poorer long‐term health‐related quality of life in comparison to spontaneous vaginal delivery. Further longitudinal studies are needed to understand the magnitude, trajectory, and underpinning mechanisms of health‐related quality‐of‐life outcomes following different modes of delivery.